TiO2 Nanoparticles In Situ Formed on Ti3C2 Nanosheets by a One‐Step Ethanol‐Thermal Method for Enhanced Reversible Lithium‐Ion Storage. Issue 10 (12th March 2020) - Jia, Lin; Li, Yali; Su, Lijun; Liu, Dequan; Fu, Yujun; Li, Junshuai; Yan, Xingbin; He, Deyan
Abstract: MXenes, a family of two‐dimensional (2D) carbides, nitrides and carbonitrides, have been considered as promising anode materials for lithium‐ion (Li + ) batteries due to their good flexibility and conductivity. Herein, we report a one‐step ethanol‐thermal method to form titanium dioxide (TiO2 ) nanoparticles on the surface of Ti3 C2 nanosheets with less oxidation and high 2D structural integrity, and meanwhile investigate the properties of reversible Li + storage. It indicates that a reversible specific capacity of 257.3 mAh g −1 at the current density of 50 mA g −1 can be delivered. Moreover, the specific capacity of 141.4 mAh g −1 with the coulombic efficiency of ∼100 % can be obtained even after 250 cycles at the current density as high as 1 A g −1 . The improved capacity can be attributed to the synergetic effect that prevents stacking of the Ti3 C2 nanosheets by the surface‐anchored TiO2 nanoparticles and meanwhile avoids agglomerating of TiO2 nanoparticles due to the existence of Ti3 C2 nanosheets. Abstract : We report a one‐step in situ ethanol‐thermal method to grow titanium dioxide (TiO2 ) nanoparticles on the surface of Ti3 C2 nanosheets with less oxidation and high 2D structural integrity. The resulting TiO2 /T−Ti3 C2 composite delivers a higher reversible specific capacity of 257.3 mAh g −1 at the current density of 50 mA g −1 compared with H−Ti3 C2 and TiO2 .